iNemo for interactive digital media‏ - Ling, Willy Zi Yuan. (2013)
The iNemo device is a newly built device created by STMicroelectronics with the aims of bringing technology to an entirely new level. Equipped with various sensors including and not limited to a magnetometer and gyroscope, we will examine the various ways we can tap on the available sensors to create an innovative product that will be useful in this age. Coupled with a growing demand and usage of smart phones across the world, we will look at the various ways of incorporating the sensors with this demand. In this thesis, we will identify the various mediums that can possibly work on the iNemo with respect to the development of an interactive digital media in a new age environment, and create a working prototype for its use on a mobile phone.